Pentingnya Etika Siber pada Era Digital - Dimas Abimanyu Prasetyo; Farhan Dwi Setiawan; Jeremiah Marvin Kapoyos; Mochamad Reyhan Gusnaldi; Wildan Hamzah Nur Fadholi; Nurfiyah (PT. Inovasi Teknologi Komputer, 2024)
Masalah etika terkait berkomunikasi digital, juga dikenal sebagai